Thermoreversible gel for intrapocket delivery of green tea catechin as a local drug delivery system: An original research - M Yuvaraja; N Raghavendra Reddy; P Mohan Kumar; K S Ravi; Nabeeh Alqahtani (Wolters Kluwer Medknow Publications, 2016)
The periodontal therapies along with systemic antibiotic therapy aim at eliminating the subgingival microbiota to arrest the progression of periodontal diseases. The complete elimination is often difficult, and thus the probability of repopulation after periodontal therapy is also high. The objectives of the study are to develop in situ thermoreversible gelling system of green tea catechins suitable for periodontal pocket administration, which would act as an adjunct to mechanical periodontal therapy. Gel is prepared on a weight basis using a cold process. In vitro drug release pattern is observed through spectrophotometer analysis at 277 nm. The gel is subjected to serial dilution analysis to determine the minimum inhibitory concentration (MIC) and disc diffusion analysis to determine the in vitro antibacterial effectiveness. Release pattern studies showed a complete release of drug from gel occurred by 36 h. A volume of 1.25 mg/ml was determined as MIC required against the periodontal pathogens. Disc diffusion analysis showed a 14 mm zone of inhibition is present around the 75 µl well for all the four species and 12 mm zone of inhibition around the 50 µl well. The advantage of F-127 is its thermoreversible nature that used for in situ gel formulation. Pluronic gel proved to be a promising carrier for prolong and effective release of green tea catechin.